Prophylactic Onlay Mesh Implantation During Definitive Fascial Closure After Open Abdomen Therapy (PROMOAT): Absorbable or Non-absorbable? Methodical Description and Results of a Feasibility Study - Schaaf, Sebastian; Schwab, Robert; Güsgen, Christoph; Willms, Arnulf (Frontiers in Surgery, 2020)
Introduction: Incisional hernia development after open abdomen therapy remains a common complication on the long run. To prove the feasibility of absorbable and non-absorbable synthetic meshes as prophylactic onlay and their impact on incisional hernia rate, we conducted a pilot study and describe our method of prophylactic onlay mesh implantation with definitve fascial closure after open abdomen therapy (PROMOAT). Material and Methods: Ten patients were prospectively enrolled and prophylactic onlay mesh (long-term absorbable or non-absorbable) was implanted at the definitive fascial closure operation. The cohort was followed up with special focus on incisional hernia development and complications. Results: OAT duration was 21.0 ± 12.6 days (95% CI: 16.9 - 25.1). Definitive fascial closure was achieved in all cases. No incisional hernias were present during follow-up interval of 12.4 ± 10.8 months (range 1-30 months). Two seromas and one infected hematoma occurred. Outcome did not differ between mesh types. Conclusion: Prophylactic onlay mesh implantation after OAT is safe and feasible. However, long-term data and large-scaled prospective studies are needed to draw conclusions for routine use.